2018
DOI: 10.1007/s00426-018-1045-0
|View full text |Cite
|
Sign up to set email alerts
|

No sex difference in an everyday multitasking paradigm

Abstract: According to popular beliefs and anecdotes, females best males when handling multiple tasks at the same time. However, there is relatively little empirical evidence as to whether there truly is a sex difference in multitasking and the few available studies yield inconsistent findings. We present data from a paradigm that was specifically designed to test multitasking abilities in an everyday scenario, the computerized meeting preparation task (CMPT), which requires participants to prepare a room for a meeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…In other words, it may be easier for women than men to divide their attention while still signaling psychological availability. Although the body of literature on gender differences with regard to multitasking is mixed (e.g., see Hirnstein et al, ), these studies typically entail memory recall, spatial abilities, and other experimental designs in a laboratory; we are unaware of any studies that have examined multitasking proficiency differences by gender in the context of childcare or psychosocial interactions. That said, Greenhaus and Beutell (), as well as others, have argued that more salient roles will tend to interfere with less salient roles more often than the reverse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it may be easier for women than men to divide their attention while still signaling psychological availability. Although the body of literature on gender differences with regard to multitasking is mixed (e.g., see Hirnstein et al, ), these studies typically entail memory recall, spatial abilities, and other experimental designs in a laboratory; we are unaware of any studies that have examined multitasking proficiency differences by gender in the context of childcare or psychosocial interactions. That said, Greenhaus and Beutell (), as well as others, have argued that more salient roles will tend to interfere with less salient roles more often than the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have argued that women are better multitaskers than men (e.g., Stoet, O'Connor, Conner, & Laws, ), but empirical evidence in support of this claim is limited. Other studies have found that men are better at multitasking or that there are no meaningful gender differences (e.g., Buser & Peter, ; Hirnstein, Larøi, & Laloyaux, ; Mäntylä, ). In any case, it is more plausible that gender differences are linked to differences in mothers' and fathers' involvement with children.…”
Section: Goal and Scope Of The Present Studymentioning
confidence: 98%
“…Studies systematically exploring gender differences in task-switching and dual-task situations are rare and their findings are heterogeneous [12]. On the one hand, some studies reported neither gender differences in sequential nor in concurrent multitasking performance [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Studies systematically exploring gender differences in task-switching and dual-task situations are rare and their findings are heterogeneous [12]. On the one hand, some studies reported neither gender differences in sequential nor in concurrent multitasking performance [1214]. For instance, Paridon and Kaufmann (2010) conducted a dual-task study where subjects performed a driving simulation task (i.e., lane-change-task with lane deviation as the dependent variable) either in isolation or in temporal overlap with another task, such as, for example, dialing a number on a mobile phone, taking a tissue out of its packet, or reading directions [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation